Investigation of Voltage Quality and Distribution Capacity Issues on Long Rural Three Phase Distribution Lines Supplying SWER Systems - Mayer, J.; Hosseinzadeh, N.; Wolfs, Peter (University of Tasmania, 2005)
Single wire earth return (SWER) electric distribution feeders are used extensively in remote parts of Queensland and other states, as an economic means to deliver electrical energy to small customer loads, scattered sparsely over vast areas. These SWER systems are normally supplied from very long (> 100 km) three phase distribution feeders. Due to recent strong load growth, voltage quality issues have arisen in these systems including voltage regulation, voltage unbalance, and phase unbalance. Excessive system power losses are also experienced. There are several available methods to combat these issues; however, some have not been applied to this type of distribution system before. Developing simple, economic solutions to these problems is likely to dramatically improve customer power quality, resulting in reduced customer complaints, whilst improving distribution capacity and reducing losses. The emphasis of this research project is the power system modelling to assess available technologies applied to this type of distribution system. The project is being undertaken in conjunction with Ergon Energy Corporation in Central Queensland so that real field data can be used to validate theoretical models.